The transition from elite junior track-and-field athlete to successful senior athlete: Why some do, why others don't - Hollings, S. C.; Mallett, C. J.; Hume, P. A. (International Journal of Sports Science and Coaching, 2014)
Guiding athletes to become senior international athletes is consistent with the brief of talent development programmes. The transition from junior to senior athlete might be viewed as a normative transition. Nevertheless, this transition is likely to be a complex process and some understanding of that complexity is necessary to inform those responsible for developing talent. This study aimed to determine why some elite junior athletes make the transition to become successful senior athletes, while others of similar ability did not. Five male and six female New Zealand athletes who made a final for their event at a World Junior Athletics Championships (WJC) between 1992 and 2006 were interviewed. Five athletes subsequently went on to win a medal or make the final of their event at an Olympic Games or World Athletics Championships or win a medal at a Commonwealth Games, while the other six continued in the sport for six to ten years as a senior athlete but did not go on to represent New Zealand internationally at the senior track-and-field international level. The data were examined using hierarchical content analysis. Athletes who progressed to become successful senior athletes displayed: i) a significant commitment to a clearly defined and realistic goal; ii) achieved early international success at the senior grade; and iii) had a single dominant identity and key strength. The athletes who did not go on to be a senior international athlete were characterised as having: i) competing demands and tensions in their social, academic/career lives, and ii) a lack of progression.